Competency of National Dual Training System Industry Advisors - Baser, Jamil Abd; Mat Jizat, Nur Atikah; Nur Yunus, Faizal Amin; Rahim, Mohd Bekri; Abdul Razzaq, Abdul Rasid; Hasan, Azman (Faculty of Engineering, Universitas Negeri Yogyakarta, 2017)
National Dual Training System (NDTS) is a system of training between the public and the private sector to produce competitive workers (k-worker) who meet the industry needs. This system consists of day release approaches that mean trainees undertake practical studies for four days and one day they receive theories while block release means trainees undertake practical studies for four months in industries and one month they receive theories. This study aimed to determine the advisors’ level of knowledge, skills, attitudes and their relationship with gender and work experience in the NDTS. This descriptive study used questionnaires with a likert scale as an instrument involving 84 respondents of qualified NDTS advisors. The data were analyzed using SPSS 21.0 and the results showed that the advisors had high knowledge, skills and attitudes. The inference analysis showed there was not difference of the level of knowledge, skills and attitudes based on advisors’ gender and the pearson correlation analysis showed that there was not relation between the advisors’ competence and work experience.